Soil Physical Properties, Carbon dioxide Emissions and Their Relationships under Different Management Systems in Semi-arid Region of Eastern Tunisia - Amami, Roua; Ibrahimi, Khaled; La Scala Júnior, Newton [UNESP]; Hmila, Amira; Abrougui, Khaoula; Chehaibi, Sayed (Taylor & Francis, 2021)
In agricultural systems, soil carbon dioxide emissions and physical properties are thought to depend largely on management practices. This field study was carried out in a semi-arid region of eastern Tunisia to evaluate the effects of tillage management on soil carbon dioxide emissions and related physical properties; bulk density (BD), penetration resistance (PR), total porosity (TP) and air-filled porosity (AFP). Tillage management treatments included plowing with a moldboard plow or a disk plow to different depths, described here as shallow (10 cm), medium (15 cm) and deep (25 cm). No-tillage was also considered as a control plot. Correlation analysis was used to explore how soil carbon dioxide emissions (CO2) were related to the other studied properties. The results showed higher carbon dioxide (CO2) emissions (p < .05) from tilled soil compared to no-till (NT), regardless of the tillage management. No significant differences in carbon dioxide (CO2) emissions were found between moldboard and disk plow tillage at the same tillage depth. Soil carbon dioxide release was the highest after deep tillage (moldboard = 0.101 t ha−1 and disk plow = 0.107 t ha−1) suggesting that deeper tillage to 25 cm promoted higher carbon dioxide (CO2) emissions. Significant differences with tillage were observed in bulk density (BD) and penetration resistance (PR) compared to no-tillage. Correlations of carbon dioxide emissions to soil physical properties across all the tillage treatments indicated significant negative relationships between carbon dioxide (CO2) emissions and soil bulk density (BD) and penetration resistance (PR) and significant positive relationships between carbon dioxide (CO2) and total porosity (TP) and air-filled porosity (WFP) suggesting that these soil attributes are important controlling factors of carbon dioxide (CO2) emissions.
Keywords: carbon dioxide emissions; correlation; Key-words; physical properties; semi-arid Tunisia; tillage management